Qualidade de vida e religiosidade de mulheres com câncer de mama em tratamento quimioterápico - Carvalho, Paula Natasha Rodrigues Valentim (2014)
Women with breast cancer undergoing chemotherapy treatment present feelings of sadness, anxiety, exclusion, and mutilation given the side effects of chemotherapy drugs, and often they find in religion the support they need to improve their mental health and thus enhance their quality of life. This study aimed to assess the influence of religiosity on the quality of life of women with breast cancer undergoing chemotherapy. It is a descriptive, exploratory, cross-sectional study conducted in specialized institution comprising 150 women. Two scales were applied: the World Health Organization Quality of Life Scale Brief Version (WHOQOL-BREF) and the Duke University Religion Index (DUREL). Results revealed that most women participating in this study were aged 46-55 years, had a partner, with three or more children, Catholic, received some financial income, had 1-4 years of study, claimed to be Brown, were mastectomized, presented stage III cancer, and Taxol was the chemotherapy regimen. With regard to the domains of quality of life, those who showed higher scores were the physical and environmental, while the lowest were the psychological and social relationships. As the scores of intrinsic religiosity increase, that is the individual religious activity reduces, the scores for the physical domain will decrease. Furthermore, women who usually go to church, temple or religious gatherings are generally those who underwent some surgical procedure, particularly mastectomy. In general, women in this study reported a good quality of life and were satisfied with their health. Nevertheless, we noted that when women diminish the individual religious activities, they present reduced quality of life. Therefore, we concluded that women with decreasing individual religious activities show reduced quality of life.